The analysis of flouting maxim in Good Morning America (GMA) talkshow - Rofa Marlisa; Didin Nuruddin Hidayat (Universitas Islam Negeri Banda Aceh, 2020)
The present study is an analysis of the flouting maxim in Good Morning America (GMA) talk show in which Jackie Chan was invited as the guest star. The goals of this research are to find out the performed flouted maxim(s) by the hosts and the guest and to reveal the reason(s) behind the occurrence of the maxim(s). In this study, the researchers employed the qualitative method and data were collected from a video. The transcript text of the utterances between the hosts and Jackie Chan as a guest consisting of flouting maxim was the instrument of this research. Then, to find and analyze the flouting maxim showed in the video, the researchers used Grice’s theory, the Cooperative Principles consisting of four maxim types: quality, quantity, relation, and manner. The result showed that all four types of maxim flouting were committed by both Jackie Chan and the two hosts of the GMA talk show. The highest flouting maxims found were flouting the maxim of quantity and manner. Further, the study also revealed the rationales behind maxims flouting which were beneficial to build fun communication and to elaborate more explanations.